Forms, methods and means of protection of the right to compensation of normal damage caused in labor relations - Gayevy, V. (Київський національний університет імені Тараса Шевченка, 2019)
The article is devoted to the study of forms, methods and means of protection of the employee's right to compensation for non-pecuniary damage inflicted in labor relations. Particular attention is paid to the analysis of the concepts of "forms", "methods" and "means" of protecting the right to non-pecuniary damage under labor law and their objective expression in practice.

Стаття присвячена вивченню форм, способів та засобів захисту права працівника на відшкодування моральної шкоди, завданої у трудових відносинах. Особлива увага приділяється аналізу понять «форм», «способів» та «засобів» захисту права на відшкодування моральної шкоди в рамках трудового права та їх об’єктивного вираження на практиці.
Форми, способи та засоби захисту права на відшкодування моральної шкоди, завданої у трудових відносинах
Keywords: means of protection; methods of protection; labor relations; forms of protection.; засоби захисту; способи захисту; трудові правовідносини; форми захисту.